KEMAJUAN PERSALINAN DENGAN MENGGUNAKAN BIRTH BALL PADA IBU BERSALIN PRIMIGRAVIDA DI PMB RENNY INDAH SARI - Retia Mufti, Iga (Institut Kesehatan dan Teknologi Al Insyirah, 2024)
Background: One of the complications of childbirth that contributes to maternal and infant mortality is prolonged labor. The survey results found that prolonged labor can cause emergencies is mothers and babies. Birth ball is a physical therapy ball that helps mothers in labor during the first stage of labor Purpose: To find out the effect of birth balls on the progress of labor in promigravida mothers at PMB in 2023 Method: The research method used is Quasi Experiment. Data collection used total sampling with a sample of 30 mothers giving birth. By using a static group comparison research design or static group comparison where this design applies treatment or intervention (X) followed by a second measurement or observation. The results of the onservations in the control group, which did not receive the intervention Result: The results of this study showed that the average progress of labor in the intervention group was 292.33 minutes, and in the control group the average progress of labor was 419 minutes. Conclusion: The conclusion of this study is that there is an effect of the birth ball on the progress of labor in primigravida mothers in the first active phase as evidenced by the t-test p-value 0,000<0,5.